KEMAMPUAN MENULIS PUISI SISWA KELAS VIII SMPN 1 LEMBAH GUMANTI DENGAN MENGGUNAKAN MEDIA POSTER - Susanti, Erlina; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
This research was motivated by three issues, namely (1) lack of students interest in learning to write poetry, (2) the delivery of learning materials of writing poetry was less interesting, (3) the inapropriate selection and use of instructional media. This research was aimed to describe the ability to write poetry of class VIII students of SMPN 1 Lembah Gumanti using media poster. This research was quantitative using descriptive methods. Research object were class VIII students of SMPN 1 Lembah Gumanti. Samples were class VIII students of SMPN1 Lembah Gumanti amounted to 33 people. The ability to write poetry class VIII students of SMPN1 Lembah Gumanti using combined media posters for both indicators is classified as Good. Based on the results of research, it can be summarized as follows: First, the use of media posters in learning to write poetry in class VIII students of SMP 1 Lembah Gumanti is classified as Good. Second, in general the average value of the ability to write poetry class VIII students of SMPN 1 Lembah Gumanti valley is 79,1 with Good qualification. The Conclusion were relevant to research, two things are recommended. First, the ability to write poetry class VIII students of SMPN1 Lembah Gumanti required further improvement. Second, the use of instructional media, should be used functionally in learning to write poetry.